Study on selected tourism events - Mohd Hanafiah, Mohd Hafiz; Othman, Nor'ain; Madzhar, Mazlina (2011)
Festivals and special events have always been associated with tourism as tourism has been recognized as one of the leading growth sectors in international services trade. Tourism events are now gradually being observed more as a vital element of Malaysian economic development. The purpose of this study is to measure the motivation, satisfaction and economic impact of the 3rd Putrajaya International Hot Air Balloon Fiesta 2011 and Thaipusam Festival 2011.The study explains and identifies the demographics profiles and the spending patterns of the international tourist visiting the 3rd Putrajaya International Hot Air Balloon Fiesta 2011 and Thaipusam Festival 2011. The data were gathered by using questionnaires and 1892 respondents that attended both event were randomly selected and surveyed. The findings of this study elucidated the level of motivation, satisfaction and economic impact of the 3rd Putrajaya International Hot Air Balloon Fiesta 2011 and Thaipusam Festival 2011 and at the end of this paper, some recommendations were discussed.